2008
DOI: 10.1016/j.geoderma.2008.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Comparing local vs. global visible and near-infrared (VisNIR) diffuse reflectance spectroscopy (DRS) calibrations for the prediction of soil clay, organic C and inorganic C

Abstract: a b s t r a c t a r t i c l e i n f oLocal, field-scale, VisNIR-DRS soil calibrations generally yield the most accurate predictions but require a substantial number of local calibration samples at every application site. Global to regional calibrations are more economically efficient, but don't provide sufficient accuracy for many applications. In this study, we quantified the value of augmenting a large global spectral library with relatively few local calibration samples for VisNIR-DRS predictions of soil cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
110
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(119 citation statements)
references
References 15 publications
(50 reference statements)
8
110
1
Order By: Relevance
“…Although there have been extensive studies of the VNIR estimation of SOM content, it is generally agreed that most of the models are location-dependent and data-specific [13,19,20]. A frequently asked question by the potential users of VNIR models for SOM estimation is: will a model calibrated from samples in a certain location work in other locations?…”
Section: Introductionmentioning
confidence: 99%
“…Although there have been extensive studies of the VNIR estimation of SOM content, it is generally agreed that most of the models are location-dependent and data-specific [13,19,20]. A frequently asked question by the potential users of VNIR models for SOM estimation is: will a model calibrated from samples in a certain location work in other locations?…”
Section: Introductionmentioning
confidence: 99%
“…Vasques et al, 2010;Sankey et al, 2008a). Shi et al (2015) proposed the use of both spectral similarities and geographically constrained local calibrations to predict soil organic C content.…”
Section: Development Of Spectral Librariesmentioning
confidence: 99%
“…They are 'spiking', which uses several local spectra to augment 10 the calibration made with an ESL (e.g. Guerrero et al, 2010;Sankey et al, 2008b;Viscarra Rossel, R.A. et al, 2009), and spiking with extra-weighting (Guerrero et al, 2014a), which uses multiple copies of the local samples to improve their leverage in the calibrations. Guerrero et al (2014a) showed that the approach improved on spiking and suggested it might be more appropriate with larger spectral libraries.…”
Section: Development Of Spectral Librariesmentioning
confidence: 99%
“…It is interesting to note that Model 3 (developed in Pineland and Psamments), which had the highest variability in TC among field sites, performed poorest in terms of transferability to other Spiking of a spectral model with local samples has been suggested to improve soil predictions (Sankey et al, 2008;Wetterlind and Stenberg, 2010) though its success is highly dependent on multiple factors including the ratio between the 'number of spike samples' and 'number of samples in the spectral library', characteristics of the soil attribute and spectral domain spaces, and the methods used to develop spectral-based soil prediction models. Although the same constraints, mechanisms, and effects impact spiking and scaling of chemometric models, the aims are inherently different.…”
Section: Soil Attribute Domain Spacementioning
confidence: 99%